Imprinted monoliths: Recent significant progress in analysis field - Wei, Ze-Hui; Mu, Li-Na; Huang, Yan-Ping; Liu, Zhao-Sheng (TrAC, Trends in analytical chemistry (Regular ed.), 2017)
Imprinted monoliths are highly selective and cost-effective materials, which have attracted significant interest in various areas, mostly as the stationary phase used in high performance liquid chromatography (HPLC) and capillary electrochromatography (CEC). This review focuses on the recent significant progress of the imprinted monoliths in preparations and applications. Some thoughts on perspectives of imprinted monoliths are also expressed. •Various new synthetic technologies and strategies for imprinted monoliths are reviewed.•The latest applications of imprinted monoliths in complex sample matrices are displayed.•Some thoughts on perspectives of imprinted monoliths are also presented.